Selected factors influencing the level of physical activity in the elderly - Wyszyńska, Justyna; Dereń, Katarzyna; Hausner, Iwona; Mazur, Artur (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. It is commonly known that physical activity has great influence on the quality of life and health in the people of all age groups. Physical activity has a beneficial influence on both functional and locomotive abilities, the dynamics of which deteriorates during the process of aging, and this in turn has an impact upon satisfaction of basic biological, social and psychological needs. Aim. The main purpose of this study was an assessment of selected factors affecting the level of physical activity in the elderly. Material and methods. The study group consisted of 100 participants (85 women and 15 men), aged from 65 to 69 years old. An International Physical Activity Questionnaire (IPAQ) - Polish long version was used. Results. A high level of physical activity was reached by 44 participants, moderate level of physical activity was noted in 53 participants, and low in physical activity was found in 3 participants. Older the subjects reached lower MET value in case of job-related physical activity and higher MET value in case of physical activity in free time and total intense effort. Conclusion. The level of job-related physical activity, the level of physical activity in free time and the total intense level of activity depended on the age of the subjects. There were no association between the level of total physical activity and sex, place of residence and BMI of participants.
Keywords: physical activity; older people; factors